A Study on Shelf Life Prolonging Process of Chili Soy Sauce in Malaysian SMEs' (Small Medium Enterprise) - Mat Sharif Z.B.; Mohd Taib N.B.; Bin Yusof M.S.; Bin Rahim M.Z.; Bin Mohd Tobi A.L.; Bin Othman M.S. (Institute of Physics Publishing, 2023)
Sodium; Chemical preservatives; Microbiological analysis; Shelf life; Small medium enterprise; Sodium benzoate; Soy sauce; spicy; Total plate count; Benzoic acid